Cool school story - Jones, Katina Z.; D'Andrea, Deborah; Ottinger, Jon; Zaidan, Rick (Akron, OH : Playhouse Publishing, 2001)
Little Lucy and her dog classmates use their imaginations to turn a story-building activity into an adventure with the help of Miss Bowser's magical word bones.
Keywords: Dogs -- Fiction; Imagination -- Fiction; Storytelling -- Fiction; Magic -- Fiction; Schools -- Fiction